Equação de 1º grau : uma proposta de ensino e de aprendizagem utilizando jogos - Castoldi, Luciana (2016)
Teaching Mathematics is much more than simply working with formulas, but it is, in fact, preparing students not only to develop critical thinking and decision making skills, but also to live in society, however, for that, it is up to the teacher to worry about presenting integrated and meaningful learning experiences. This research addresses the influence of games on the development of first-degree equation concepts with the 7th and 8th year groups. This stage of education is very important for the development of these concepts. So, the teacher should provide an attractive environment, as well as practices which arouse the students interest, what ends up leading the teacher to reconsider his pedagogical practice. The use of games is cogitated by many scholars as an important resource for learning to occur as a meaningful and pleasurable way. Thus, this study aimed to ascertain whether the use of games trend helps effectively in the teaching and learning process. During this research, three games were addressed: Algebra Memory , Language Domino and On the trail of the equation . After the application of all the games and activities, an analysis of the activities used during the study was made in order to verify whether the proposed objective was achieved. Subsequent to the analysis of all collected material, we can find that the use of the games in the classroom, helped the students to understand mathematical concepts, besides allowing interactions among them so that socialization, dialogue, and mutual aid were predominant in the performing of all the activities. Moreover satisfaction and motivation with the games were visible, what is important for the learning development, in addition to that, the games have made students develop the habit of seeking solutions to the proposed situations without the need for a ready formula. From the foregoing, we consider that the chosen games reached satisfactorily, the aim of this research, as with the use of games students have become more critical and confident, and also changed their attitude towards school and the negative image they had about mathematics. Finally, we point out that this teaching methodology became more meaningful to students, while taking part in their own knowledge, the student becomes an active agent in the construction of knowledge and not just a receiver. So we suggest that this method to be discussed in front of other content, because with this research we observed that the use of games helped students understand mathematical concepts